Antimicrobial resistance. New antimicrobial agents in the treatment of chronic trophic ulcers - Frolova, Aelita; Kosinets, Alexander (Lietuvos chirurgija, 2015)
Background / objectiveThe steady growing number of pathogenic microorganisms resistant not only to antibiotics but also to antiseptics complicates the cure of the wound process. The sensibilization of skin to the majority of locally applicable preparations creates certain difficulties in the treatment of chronic trophic ulcers. The new herbal remedy PhytoMP was developed based on two components (Macleaya microcarpa (Maxim.) Fedde, Papaveraceae family and Plantago major L., Plantaginaceae family). A new atraumatic combined dressing was developed based on polyester curtain nets coated with copper particles 0.2 mcm in size and a linen nonwoven sorbent containing silver nanoparticles stabilized by PhytoMP. The aim of the present study was to investigate the possibility of these developments to improve the effectiveness of the complex therapy of trophic ulcers of the lower limbs.MethodsA clinical trial study was conducted in the Republic Center of Surgical Infection, Belarus. Patients (n = 42) with chronic trophic ulcers of the lower limbs participated in the study. The sensitivity of microorganisms to antibiotics, herbal remedy, and metallic fabrics was determined by the method to diffusions in agar. By the method of the dose- and time-dependent killing of pathogens, the minimal inhibitory concentration for PhytoMP and the duration of its antimicrobial effect was evaluated. The total treatment response was evaluated on the basis of changes in the clinical manifestations of the disease, according to the subjective feelings of patients, the degree of bacterial contamination, the terms of the appearance of granulation, epithelialization, healing, and the cytological picture. The parameters were evaluated before the treatment and every third day in the period until complete ulcer healing. The data were analyzed statistically.ResultsBacteriological examination revealed that the microflora of trophic ulcers in 37.04% of cases was introduced by S. aureus which was resistant to the majority of antibiotics. A comparative analysis demonstrated the significant differences in terms of a complete cleansing of ulcers from pathogens: with use of PhytoMP on the 7.38 ± 0.65 day, while in the control group it was on 8.30 ± 0.48 day (p < 0.01). The average hospital stay of patients with trophic ulcers from the main group was 30.77 ± 2.01 bed-days and from the control group 35.50 ± 1.72 bed-days (p < 0.01). It was experimentally established that the use of PhytoMP infusion as a matrix for stabilizing silver nanoparticles allows to halve the amount of the metal in a linen nonwoven sorbent, and to achieve a strong antimicrobial effect against S. aureus and E. coli. It was noted that, due to the strong antimicrobial effect, the physical properties of the developed combined dressings, their high anti-adhesive activity allowing carrying out the atraumatic change of bandage without moving a flap, successful results of skin plastic were observed.ConclusionsThis study suggests that the developed herbal remedy PhytoMP and atraumatic combined dressings are a promising alternative to be used in the treatment of chronic trophic ulcers.
Keywords: chronic trophic ulcers; wound infection; PhytoMP; dressings; nanoparticles